Simulação numérica de fluxo de águas subterrâneas na bacia do Rio Corrente (BA) - Engelbrecht, Bruno Zanon [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The numeric simulation is an important tool applied in understanding the dynamics of groundwater flow. In a hydrogeological model the processes responsible for groundwater flow are described by numerical formulations that allow the simplification, representation and understanding of the dynamics of the Aquifer System. In this work, a steady state groundwater flow simulation of Urucuia Aquifer System (UAS) part of the Corrente river basin was conducted, using the finite element method through software FEFLOW, to understand the dynamics of groundwater flow and quantify the hydrologic balance. The aquifer system Urucuia lodges in the São Francisco hydrogeological province and corresponds to a set of interconnected aquifers that occur in rocks from Urucuia group in the Urucuia sub-basin described by Campos e Dardenne (1997). The system is a porous media one, in a shape of a thick table mountain, consisting essentially of sandstones. The Corrente river basin is located in UAS in Western State of Bahia and it's one of the main units to maintaining permanent flow (Q95) and average natural flow of the São Francisco river. The simulation performed in this work obtained the following results for the modelled region: horizontal hydraulic conductivity of 3 x 10-4 m/s and vertical one 6 x 10-5 m/s; maximum recharge of 345 mm and minimum of 85 mm/a. It was concluded that: (1) regional groundwater flow has eastbound; with an exception of the extreme northeast portion, where the flow has opposite direction; (2) there are smaller water side dividers with an approximate direction EW, that guide the flow of water to the drainage that cut the aquifer; and (3) the UAS at Corrente river basin can be understood as a free regional aquifer system, isotropic and homogeneous. Regionally, the small lithological variations present in the Urucuia group can be neglected and do not exhibit significant influences on the dynamics of ground water flow

A simulação numérica é uma importante ferramenta aplicada na compreensão da dinâmica do fluxo das águas subterrâneas. Em um modelo hidrogeológico os processos responsáveis pelo fluxo de águas subterrâneas são descritos por formulações numéricas que permitem a simplificação, representação e entendimento da dinâmica do Sistema Aquífero. Neste trabalho foi realizada uma simulação de fluxo de águas subterrâneas em regime permanente na porção do Sistema Aquífero Urucuia (SAU) da bacia do rio Corrente, utilizando o método dos elementos finitos através do software FEFLOW, visando compreender a dinâmica do fluxo de águas subterrâneas e quantificar seu balanço hidrológico. O sistema aquífero Urucuia aloja-se na província hidrogeológica São Francisco e corresponde ao conjunto de aquíferos interligados que ocorrem nas rochas do Gr. Urucuia na sub-bacia Urucuia descrita por Campos & Dardenne (1997). O sistema é do tipo intergranular, na forma de um tabuleiro espesso, constituída essencialmente por arenitos. A bacia do rio Corrente localiza-se no SAU no oeste do estado da Bahia e é uma das principais unidades para a manutenção vazão permanente (Q95) e natural média do rio São Francisco. A simulação realizada neste trabalho obteve os seguintes resultados para a região modelada: condutividade hidráulica horizontal de 3x10-4 m/s e vertical de 6x10-5 m/s; recarga máxima de 345 mm/a e mínima de 85 mm/a. Concluiu-se que: (1) regionalmente o fluxo de águas subterrâneas tem sentido leste; à exceção da porção extremo nordeste, onde o fluxo tem sentido oposto; (2) existem divisores de águas secundários de direção aproximada EW, que direcionam o fluxo de águas para as drenagens que cortam o aquífero; e (3) o SAU na bacia do rio Corrente pode ser compreendido como um sistema aquífero regional livre, isotrópico e homogêneo. Regionalmente, as pequenas variações litológicas presentes no Gr. Urucuia...
Keywords: Águas subterrâneas; Aguas subterraneas - Escoamento; Modelos matematicos; Método dos elementos finitos; Modelagem geologica; Corrente, Rio, Bacia (BA)